Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1042/bst0311423
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of fructosyl-lysine and advanced glycation end products in the kidney, retina and peripheral nerve of streptozotocin-induced diabetic rats

Abstract: The accumulation of AGEs (advanced glycation end products) in diabetes mellitus has been implicated in the biochemical dysfunction associated with the chronic development of microvascular complications of diabetes--nephropathy, retinopathy and peripheral neuropathy. We investigated the concentrations of fructosyl-lysine and AGE residues in protein extracts of renal glomeruli, retina, peripheral nerve and plasma protein of streptozotocin-induced diabetic rats and normal healthy controls. Glycation adducts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(92 citation statements)
references
References 10 publications
3
82
0
7
Order By: Relevance
“…A number of studies have suggested that renal AGE accumulation is positively linked to renal dysfunction associated with diabetes and ageing [29,30]. Our findings demonstrate that the kidneys of LPD offspring, in which there was a 28% reduction in nephron number, are more susceptible to AGE accumulation during normal ageing and accumulate AGEs more rapidly following exposure to increased circulating levels of AGEs, possibly via changes in AGE clearance receptors [38].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…A number of studies have suggested that renal AGE accumulation is positively linked to renal dysfunction associated with diabetes and ageing [29,30]. Our findings demonstrate that the kidneys of LPD offspring, in which there was a 28% reduction in nephron number, are more susceptible to AGE accumulation during normal ageing and accumulate AGEs more rapidly following exposure to increased circulating levels of AGEs, possibly via changes in AGE clearance receptors [38].…”
Section: Discussionmentioning
confidence: 51%
“…The factors leading to increased AGE accumulation in animals with a reduced number of nephrons remain to be established. In previous studies in diabetes, reduced renal filtration of circulating AGEs and increased AGE formation associated with hyperglycaemia have been linked to renal AGE accumulation in patients with diabetic nephropathy [29,30]. However, mechanisms other than GFR and dysglycaemia appear to contribute to AGE accumulation in the LPD model.…”
Section: Discussionmentioning
confidence: 94%
“…N ε -(Carboxymethyl) lysine (CML) is one well characterised glycoxidation product, which serves as a biomarker of general oxidative stress, accumulates in tissues with age and whose rate of accumulation is accelerated in diabetes [6][7][8]. ROS, in particular superoxide anions, interact with nitric oxide, forming the strong cytotoxin, peroxynitrite, which attacks various biomolecules, leading to the production of a modified amino acid nitrotyrosine [9].…”
Section: Introductionmentioning
confidence: 99%
“…Detection of protein glycation, oxidation, and nitration adducts by liquid chromatography with triple quadrupole mass spectroscopy (LC-MS/MS) has been reported previously in the quantitative screening of protein glycation, oxidation, and nitration adducts, measured as adduct residues in proteins and free adducts in physiological fluids (6). In diabetes, protein glycation adducts residues have been shown to be increased in cytosolic proteins at sites of development of vascular complications including renal glomeruli, retina, and nerves (6,19). Cells maintain the quality and functional integrity of proteins by degradation and replacement of proteins damaged by oxidation and glycation (6,20).…”
mentioning
confidence: 99%